Hegnera obcordata (Fabaceae: Desmodieae), a newly recorded genus and species for the flora of China - Jiang, Kai-Wen; Song, Zhu-Qiu; Pan, Bo; Zhao, Xue-Li; Li, Shi-Jin; Tu, Tie-Yao; Gong, Yan-Xiong (Phytotaxa, 2024)
Hegnera obcordata (Miq.) Schindl., is reported here as a newly recorded genus and species for the flora of China. It was collected from Xishuangbanna, Yunnan Province and Changjiang, Hainan Province. As a member of the tribe Desmodieae, H. obcordata can be easily distinguished from other genera by its climbing habit, depressed obovate terminal leaflet with an obcordate apex, and pods with U-shaped articles and deeply indented upper sutures. This study provides a detailed morphological description, phenology, distribution map and colored photographs of H. obcordata. Additionally, an updated dichotomous key to the Chinese Desmodieae genera is provided.